Rút gọn: A = (2√3 + 3)(√12 – 3) B = ( 1/√3 + √2 ) – ( √15 – √12/√5 – 2 )

Rút gọn:
A = (2√3 + 3)(√12 – 3)
B = ( 1/√3 + √2 ) – ( √15 – √12/√5 – 2 )

0 bình luận về “Rút gọn: A = (2√3 + 3)(√12 – 3) B = ( 1/√3 + √2 ) – ( √15 – √12/√5 – 2 )”

  1. Giải thích các bước giải:

     `A = (2\sqrt{3}+3)(\sqrt{12}-3)`

    `=(2\sqrt{3}+3)(2\sqrt{3}-3)`

    `=(2\sqrt{3})^2-3^2`

    `=12 – 9 = 3`

     `B = (1/\sqrt{3}+\sqrt{2}) – (\sqrt{15} – \sqrt{12}/\sqrt{5}-2)`

     `B = ((\sqrt{3})/(\sqrt{3}\sqrt{3})+(\sqrt{2}\sqrt{3})/(\sqrt{3}\sqrt{3})) – ((\sqrt{15}\sqrt{5}\sqrt{5})/(\sqrt{5}\sqrt{5}) – (\sqrt{12}\sqrt{5})/(\sqrt{5}\sqrt{5})-(2\sqrt{5}\sqrt{5})/(\sqrt{5}\sqrt{5}))`

    `B=(\sqrt{3}/3+(3\sqrt{2})/3)-((5\sqrt{15})/5-(12\sqrt{5})/5-10/5)`

    `B=((\sqrt{3}+3\sqrt{2})/3)-((5\sqrt{15}-2\sqrt{15}-10)/5)`

    -`B=(\sqrt{3}+3\sqrt{2})/3-(3\sqrt{15}-10)/5`

    Bình luận

Viết một bình luận